2008
DOI: 10.1097/pai.0b013e31805baa41
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated Fatty Acid Metabolizing 15-Lipoxygenase-1 (15-LO-1) Expression in Normal and Tumorigenic Human Bladder Tissues

Abstract: Diets high in fat seem to correspond with an increased risk of certain forms of cancer, including bladder BlCa. This preliminary study examined the expression and enzyme activity profile of the polyunsaturated fatty acid metabolizing enzyme 15-Lipoxygenase-1 (15-LO-1) in human tissues from normal bladder and bladder tumors (stages CIS-T3/T4). Human tissue samples from normal (donor) bladder and bladder tumors (stages CIS-T3/T4; non-Bacillus Calmette-Guerin-treated) were grossly microdissected and analyzed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Both anticarcinogenic and procarcinogenic roles have been proposed . In agreement with its tumor suppressor function, 15‐LO1 is downregulated in many human cancer types in comparison with their benign counterparts , whereas it is overexpressed in prostate cancer and its precursors . Similarly to its role in colorectal carcinogenesis , 15‐LO1 appears to function as a tumor suppressor in many other organ systems.…”
Section: Discussionmentioning
confidence: 94%
“…Both anticarcinogenic and procarcinogenic roles have been proposed . In agreement with its tumor suppressor function, 15‐LO1 is downregulated in many human cancer types in comparison with their benign counterparts , whereas it is overexpressed in prostate cancer and its precursors . Similarly to its role in colorectal carcinogenesis , 15‐LO1 appears to function as a tumor suppressor in many other organ systems.…”
Section: Discussionmentioning
confidence: 94%
“…However, immunohistochemical pathologists, such as Becker and Taylor [28], believe that immunohistochemistry-based methods retain morphological data but prove difficult to quantify, and that Western blotting may be used for quantitative detection of protein in tissue. In a study by Philips et al, both Western blotting and immunohistochemistry were used to investigate enzyme proteins in the human bladder [29]. According to Becker’s strategy and Phillips’ measurements, we applied two techniques, immunohistochemistry and Western blotting, to explore the effects of costimulatory proteins in liver.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other LOXs do not appear to be significantly altered during colonic tumorigenesis [31, 73, 74]. Downregulation of ALOX15 expression has also been reported in various other human cancers, including lung [75], esophageal [76], breast [77], endometrial [78], urinary bladder [79] and pancreatic cancer [80]. Additionally, screening of 128 different human cancer cell lines representing 20 different human cancers, including all common human cancers, showed that ALOX15 expression was markedly repressed [75].…”
Section: Alox15 Inhibits Colorectal Tumorigenesismentioning
confidence: 99%